Giant rectal fecaloma treated with carbonated soft drink and argon plasma coagulation - Philippe Attieh; Karam Karam; Elias Fiani; Ihab I. El Hajj (European Journal of Case Reports in Internal Medicine)
Constipation is a common gastrointestinal disorder affecting approximately 15% of the population, with a higher prevalence in women and older adults. It can be classified as primary, including functional constipation, pelvic floor dysfunction, and slow transit, or secondary, resulting from neurological, endocrine, metabolic disorders, cancer, or medications. In individuals over 75, constipation ranks as the seventh most common condition in primary care. A severe complication, fecal impaction, occurs more frequently in older adults and accounts for 0.03% of emergency department visits, with the highest risk in those over 85. In Parkinson’s disease, constipation is a significant nonmotor symptom affecting up to 63% of patients and may lead to complications such as intestinal obstruction and aspiration pneumonia. We present the case of a 94-year-old male with Parkinson’s disease who developed a 5 × 5 cm rectal fecaloma, unresponsive to standard endoscopic fragmentation techniques, including retrieval tools, high-pressure water jets, and polypectomy snares. Carbonated soft drink (Coca-Cola®) injection (500 ml) was used to soften the fecaloma, followed by off-label argon plasma coagulation (APC) (30–50W, 2 l/min), which successfully facilitated further fragmentation and near-total removal. This case highlights the potential role of Coca-Cola® and APC as adjunctive therapies in managing refractory fecalomas.